Long-Term Trends in Black Carbon and Aerosol Optical Depth Over the Central Himalayas: Potential Causes and Implications - Joshi, Hema; Naja, Manish; Srivastava, Priyanka; Gupta, Tarun; Gogoi, Mukunda M.; Suresh Babu, S. (Frontiers in Earth Science, 2022)
Continuous ground-based observations of aerosols over the Himalayan region are highly beneficial in studying aerosol trends over the complex geographic terrain. This study presents the results from continuous long-term observations (2004-2016) of aerosols over a high-altitude site in the central Himalayas - Nainital, quantifying multihued aspects of black carbon (BC) and columnar aerosol optical depth (AOD). The results reveal that BC and AOD have a positive trend of 23.04 ± 3.00 ng m-3 year-1 and 0.0076 ± 0.0003 year-1 respectively. Simultaneously, a positive trend of 0.0066 ± 0.0059 year-1 is observed in Angstrom exponent, thus indicating an increase in anthropogenic aerosols. The satellite observations covering a broader region around Nainital also depicted increasing trends in AOD (0.0042-0.0074 year-1), absorbing aerosol optical depth (0.0001 ± 0.0001 year-1) and aerosol index (0.0131 ± 0.0019 year-1), along with a slight decline in single scattering albedo (-0.0004 year-1). These results suggest that aerosols of absorbing nature might have increased over this region in the recent times. Investigation of AOD ratio, obtained from aerosol vertical profiles, revealed an increasing trend in aerosol load below 1 km. The observed trends in aerosols are found to be associated with the enhanced biomass burning activity, reflected in terms of the positive trend in fire count ~38.65±5.88 year-1 over the region.